Organizational Effectiveness of Family Firms in Java Island: The Role of Family Essence and Socioemotional Wealth - Nony Kezia Marchyta; Anna Safira; Clarissa Listya Susilo; Agoes Tinus Lis Indrianto (Global Action and Education for Society, 2026)
The influence of socioemotional wealth in the family business is substantial, but conflicting findings exist. Furthermore, there is a lack of research addressing it in the family business at Java Island. The research aims to analyze the relationship between family essence, socioemotional wealth, and organizational effectiveness in family businesses at Java Island. This quantitative research used a purposive sampling technique for data collection by distributing questionnaires to owners, successors, or management of family businesses in Java Island. The hypotheses were tested using Partial Least Square. The results indicate that family essence positively influences socioemotional wealth and organizational effectiveness, while socioemotional wealth positively influences organizational effectiveness. This study helps family businesses improve organizational effectiveness by identifying family essence and socioemotional wealth as essential variables to focus on. They can increase organizational effectiveness by forming a strategy based on strengthening family essence and socioemotional wealth.